Nitric oxide functions upstream of hydrogen sulfide in strigolactones-triggered stomatal closure in Arabidopsis thaliana (L.) Heynh (Bangladesh Journal of Botany, 2025)
Strigolactones (SLs)-induced stomatal closure involves nitric oxide (NO) and hydrogen sulfide (H2S) in Arabidopsis thaliana (L.) heynh. H2S synthesis inhibitors and NO modulators prohibited SL-triggered stomatal closure. SL caused stomatal closure of nia2-1 mutant, but failed to close stomata of Atl-cdes, Atd-cdes, nia1-2, nia1-2/nia2-5 and Atnoa1 mutants. SL induced NO production in wild-type and nia2-1 mutant, but not in Atnoa1, nia1-2 and nia1-2/nia2-5 mutants, NO modulators inhibited the effects induced by SL in wild-type. Furthermore, SL promoted H2S synthesis and L-/D-CDes activity in wild-type and nia2-1 mutant, NO modulators prevented the effects induced by SL in wild-type. The induction of H2S synthesis and L-/D-CDes activity by SL was abolished in Atnoa1, nia1-2 and nia1-2/nia2-5 mutants. However, H2S synthesis inhibitors could not inhibit SL-induced NO production in wild-type, Atl-cdes and Atd-cdes mutants exhibited normal NO levels in guard cells. The results suggested that NO functioned upstream of H2S synthesis in SLs-triggerred stomatal closure in A. thaliana.Bangladesh J. Bot. 54(4): 949-956, 2025 (December)